2016
DOI: 10.1097/ico.0000000000000657
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Comorbidities of Dry Eye Syndrome

Abstract: We found that patients with dry eye syndrome have a higher prevalence of several systemic comorbidities. A more comprehensive therapeutic approach considering the effect of systemic medication may be necessary in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…In addition, dry eye syndrome is more common in those who work on computers and has been reported in up to 60% of individuals who work with video monitors [ 16 ]. This prevalence is very high when considering the prevalence of dry eye syndrome in the general population is approximately 10% [ 17 ]. Although the exact mechanism of CVS is unclear, a decreased blink rate and increased accommodative effort are considered two possible underlying causes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dry eye syndrome is more common in those who work on computers and has been reported in up to 60% of individuals who work with video monitors [ 16 ]. This prevalence is very high when considering the prevalence of dry eye syndrome in the general population is approximately 10% [ 17 ]. Although the exact mechanism of CVS is unclear, a decreased blink rate and increased accommodative effort are considered two possible underlying causes.…”
Section: Discussionmentioning
confidence: 99%
“…Roh et al [ 15 ] tried to identify systemic comorbidities in patients with dry eye syndrome in South Korea ( n = 17,364), with a prevalence of dry eye of 10.4%. Degenerative arthritis (OR 1.57) and rheumatoid arthritis (OR 1.44) were associated with a significantly higher prevalence of dry eye.…”
Section: Discussionmentioning
confidence: 99%
“…It may be related that there were less women, more young people, and fewer people with chronic diseases in the group that had consumed 3 or more cups of coffee. It is well known that the risk of dry eye syndrome is higher in women, people with chronic diseases, and older individuals [ 7 , 18 - 21 ]. The cross-sectional study of Moss et al [ 13 ] also showed that men and younger people had lower risk of dry eye syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…There is a wide range of risk factors that include age, sex, postmenopausal hormone therapy experience, presence of connective tissue disease, prior refractive surgery, and exposure to various medications such as antihistamines, antihypertensive, and antidepressant [ 6 ]. Furthermore, a study in Korea has shown that residents in urban areas, people that work in offices, or those with medical conditions including hyperlipidemia, osteoarthritis, and renal failure are more at risk of dry eye syndrome [ 7 ].…”
Section: Introductionmentioning
confidence: 99%